2004
DOI: 10.1073/pnas.0308617100
|View full text |Cite|
|
Sign up to set email alerts
|

Liver-specific deletion of negative regulator Pten results in fatty liver and insulin hypersensitivity

Abstract: In the liver, insulin controls both lipid and glucose metabolism through its cell surface receptor and intracellular mediators such as phosphatidylinositol 3-kinase and serine-threonine kinase AKT. The insulin signaling pathway is further modulated by protein tyrosine phosphatase or lipid phosphatase. Here, we investigated the function of phosphatase and tension homologue deleted on chromosome 10 (PTEN), a negative regulator of the phosphatidylinositol 3-kinase/AKT pathway, by targeted deletion of Pten in muri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

52
417
3
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 396 publications
(473 citation statements)
references
References 57 publications
52
417
3
1
Order By: Relevance
“…PTEN antagonizes insulin signaling, and its deficiency leads to hepatic steatosis. 10,11 However, the PTEN protein levels were unchanged in the model (Fig. 5A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PTEN antagonizes insulin signaling, and its deficiency leads to hepatic steatosis. 10,11 However, the PTEN protein levels were unchanged in the model (Fig. 5A).…”
Section: Resultsmentioning
confidence: 99%
“…The NAFLD/NASH models that are frequently employed are classified into three categories. The first group encompasses genetic models that produce obesity because of naturally occurring null mutations of genes such as leptin, 3 leptin receptor, 4,5 and agouti, 6 and those with deranged liver metabolism due to targeted ablation of peroxisome proliferator-activated receptor ␣ (PPAR␣), 7 acyl-CoA ox-idase, 8 MAT1A, 9 and phosphatase and tension homolog deleted on chromosome 10 (PTEN), 10,11 or targeted overexpression of sterol regulatory element binding protein 1 (SREBP-1) 12 and PPAR␄. 13 Although these genetic approaches are useful in assessing biological significance of each gene product in vivo, they do not reflect the natural etiological setting of the most common form of NAFLD/NASH in patients.…”
mentioning
confidence: 99%
“…In mice, overexpression of an activated form of AKT or liver-specific deletion of PTEN leads to increased FASN expression and its mediated lipogenesis, resulting in hepatic steatosis. [33][34][35] In human HCC cells, it has been found that AKT/mTOR/RPS6 cascades promotes lipogenesis via multiple mechanisms, including increased mRNA expression of FASN and other lipogenic pathway genes, decreased FASN degradation, and augmented stability of SREBP1/2. 33 Altogether, these lines of evidence indicate that the AKT/mTOR pathway is the major regulator of lipogenesis along hepatocarcinogenesis.…”
Section: Increased Lipogenesis In Hccmentioning
confidence: 99%
“…Studies on mice with PTEN ablation in liver [13,14], adipose [15] or skeletal muscle tissues [16] have investigated the effect of PTEN on whole-body glucose homeostasis. In general, this work has provided further support for a role for PTEN in insulin sensitivity and metabolic regulation (Table 1).…”
Section: Abbreviationsmentioning
confidence: 99%
“…However, when subjected to a highfat diet, these animals showed protection against the development of hyperglycaemia and abnormalities in glucose tolerance. Cell proliferation in fat and muscle was not Liver-specific ablation Reduced fasting plasma insulin, enhanced glucose tolerance and insulin sensitivity [13,14] Fat-specific ablation Reduced fasting plasma insulin, enhanced glucose tolerance and insulin sensitivity [15] Muscle-specific ablation Protection from insulinresistance and diabetes when exposed to high-fat diet [16] Ubiquitous haploinsufficiency…”
Section: Abbreviationsmentioning
confidence: 99%